Tempo e contemporaneidade em Euclides da Cunha - Cunha, Paulo Ribeiro Rodrigues da [UNESP] (My University, 2011)
This issue focuses on racism, national identity, colonialism and intellectuals admitted by the high society that, in order to preserve themselves, avoid discussing in their Works of flaming plights of the society.

Este artigo trata de racismo, identidade nacional, colonialismo e intelectuais cooptados pela elite, que, para se preservarem, evitam tratar, em suas obras, de problemas explosivos da sociedade.
Time and contemporaneity in Euclides da Cunha
Keywords: Euclides da Cunha